Pengaruh Pembiasaan Qiro’at Al Qur’an Terhadap Kecerdasan Spiritual Siswa (Studi Kasus di SMP Islam Bustanul Ulum Ketanggungan Kabupaten Brebes) - Alawiyah, Siti; Nurhaemin, Nurhaemin; Tosuerdi, Tosuerdi; Dinarni, Dian; Sari, Ica Ratna (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study was motivated by the low level of awareness among some students at Bustanul Ulum Ketanggungan Islamic Junior High School in internalising spiritual values, even though the school has implemented a Qiro'at Al-Qur'an habit formation programme. This study aims to describe the implementation of the Qiro'at Al-Qur'an programme, identify the level of students' spiritual intelligence, and analyse the effect of the programme on students' spiritual intelligence. This study used a quantitative approach with a survey method. Data were collected through a Likert scale questionnaire given to 32 seventh-grade students. Data analysis was performed using validity tests, reliability tests, and simple linear regression. The results showed that most students were in the ‘Frequent’ category with a percentage of 52.83%, indicating a good level of spiritual intelligence. The regression test results showed a constant value of 27.853 and a regression coefficient of 0.293 with a significance value of 0.037 (< 0.05), which means that the Qiro'at Al-Qur'an habit-forming programme has a positive and significant effect on students' spiritual intelligence. Thus, the Qiro'at Al-Qur'an habit-forming programme has been proven to contribute to strengthening students' spiritual intelligence and needs to be implemented consistently and integrated into learning activities.